Analysis of Childhood Malnutrition and Disease in Bangladesh: A Cross Sectional Study in Chattogram (Journal of Chittagong Medical College Teachers' Association, 2025)
Background: Malnutrition in children is an important issue for developing countries since it has a direct impact on social and health policies. Malnutrition is one of the key public health challenges of the 21st century, and relative improvement trends in malnutrition show significant disparity, especially for South Asia. Malnutrition is associated with 1 to 2 million preventable annual child deaths and chronic illness puts children at risk of malnutrition. The magnitude of malnutrition in Bangladesh is a matter of great concern and is a complicated issue which depends on several factors. The aim of the study to determine prevalence of malnutrition in the selected participants and the causes of malnutrition in the selected participants.Materials and methods: A cross sectional study was implemented among a sample of 250 children aged 6-59 months enrolled from tertiary hospitals and government health complexes across Chattogram. The timeline of the study was from January to June 2022. SPSS was used to analyze the collected data, with the presence of acute malnutrition as the dependent variable.Results: The results show that among the 250 children enrolled for the data collection, the prevalence of Acute Malnutrition (AM) was determined to be 7.6% (n=19). Among these, one (5.3%) had Severe Acute Malnutrition (SAM) while the remaining 18(94.7) had Mild Acute Malnutrition (MAM).Conclusion: The burden of Acute Malnutrition (AM) among children under 5 years of age is still high compared to the worldwide prevalence, which is a disturbing issue for policy makers. In this study, apart from the children’s age, factors such as low protein intake, lower level of paternal education and incidences of respiratory illnesses were associated with acute malnutrition.JCMCTA 2024 ; 35 (2) : 87-94